Peran Kepemimpinan Transformasional, Budaya Organisasi, Motivasi Kerja terhadap Produktivitas Karyawan - Muhammad Haidar Affan; Novi Fitria Hermiati; Amellia Dwi Putri; Amanda Widyastuti; Pinnah Ayu Lestari (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The role of transformational leadership, organizational culture, and work motivation in improving employee productivity in manufacturing companies is discussed in this study. Companies face great challenges to maintain and improve their productivity in an era of globalization and intense competition. Employees get inspiration and motivation from transformational leadership, and a positive corporate culture encourages teamwork. To ensure that employees remain energized and dedicated, it is crucial to have high work motivation. The method used is a quantitative method involving data analysis using the Partial Least Squares Structural Equation Model (PLS-SEM). With an R2 value of 0.953, the third variable has a positive and significant impact on employee productivity. The results show that in a competitive business environment, increasing productivity through developing better leadership, improving organizational culture, and increasing work motivation is essential.